2018*x(x-2018/7)=0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\left(x+2018\right)\left(\frac{1}{2}+\frac{2}{7}\right)=\left(x+2018\right)\left(\frac{1}{5}+\frac{1}{6}\right)\)
\(\Leftrightarrow\) \(\left(x+2018\right)\left(\frac{1}{2}+\frac{2}{7}\right)-\left(x+2018\right)\left(\frac{1}{5}+\frac{1}{6}\right)\) = 0
\(\Leftrightarrow\left(x+2018\right)\left(\frac{1}{2}+\frac{2}{7}-\frac{1}{5}-\frac{1}{6}\right)=0\)
\(\Leftrightarrow x+2018=0\)
\(\Leftrightarrow x=-2018\)
b) \(7\left(x-1\right)+2x\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(7+2x\right)=0\)
\(\Leftrightarrow\) x - 1 = 0 hoặc 7 + 2x = 0
1) x - 1 = 0 \(\Leftrightarrow\) x = 1
2) 7 + 2x = 0 \(\Leftrightarrow\) -3,5
Vậy: x = 1; -3,5
b) \(7\left(x-1\right)+2x\left(x-1\right)=0\)
=> \(\left(x-1\right).\left(7+2x\right)=0\)
=> \(\left\{{}\begin{matrix}x-1=0\\7+2x=0\end{matrix}\right.\) => \(\left\{{}\begin{matrix}x=0+1\\2x=0-7=-7\end{matrix}\right.\) => \(\left\{{}\begin{matrix}x=1\\x=\left(-7\right):2\end{matrix}\right.\)
=> \(\left\{{}\begin{matrix}x=1\\x=-\frac{7}{2}\end{matrix}\right.\)
Vậy \(x\in\left\{1;-\frac{7}{2}\right\}.\)
Chúc bạn học tôt!
a: =>x-2017=0 và y-2018=0
=>x=2017; y=2018
b: =>3x-y=0 và y+2/3=0
=>y=-2/3 và 3x=-2/3
=>x=-2/9 và y=-2/3
c: =>3/4x-1/2=0 và 4/5y+6/25=0
=>x=2/3 và y=-3/10
(5^2018+5^2018+5^2018+5^2018) + 5^2018 -5x=0
5^2018+5^2018+5^2018+5^2018+5^2018-5x =0
5(5^2018)-5x =0
5x =5(5^2018)-0
5x =5(5^2018)
Suy ra x= 5^2018
Vậy: x= 5^2018
Câu a :
\(5x\left(x-2018\right)-x+2018=0\)
\(5x\left(x-2018\right)-x+2018=0\)
\(\Leftrightarrow5x\left(x-2018\right)-\left(x-2018\right)=0\)
\(\Leftrightarrow\left(x-2018\right)\left(5x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-2018=0\\5x-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=2018\\x=\dfrac{1}{5}\end{matrix}\right.\)
Vậy \(x=\dfrac{1}{5}\) hoặc \(x=2018\)
Câu b :
\(x^3-2x=0\)
\(\Leftrightarrow x\left(x^2-2\right)=0\)
\(\Leftrightarrow x\left(x-\sqrt{2}\right)\left(x+\sqrt{2}\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x-\sqrt{2}=0\\x+\sqrt{2}=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=\sqrt{2}\\x=-\sqrt{2}\end{matrix}\right.\)
Vậy \(x=-\sqrt{2}\) ; \(x=0\) hoặc \(x=\sqrt{2}\)
Wish you study well !!